2017
DOI: 10.2196/resprot.7491
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Avoidance for Children in REpública Dominicana (SACRED): Protocol for a Prospective Study of Stroke Risk and Hydroxyurea Treatment in Sickle Cell Anemia

Abstract: BackgroundIn the Dominican Republic, where the burden of sickle cell anemia (SCA) is high, many children lack access to routine screening and preventative care. Children with SCA are at risk for stroke, an event that leads to significant morbidity and mortality. In the United States, screening via transcranial Doppler (TCD) identifies children with SCA at highest stroke risk, allowing early intervention with blood transfusions. The need for indefinite transfusions for primary stroke prevention limits their pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…HU's effectiveness will be determined by comparing the baseline and potentially reduced TCD velocities. Preliminary study results from the SACRED study identified a higher prevalence of conditional TCD and lower abnormal TCD, which the investigators suggest could be attributed to differences in baseline status, prior treatment effects, or genetics [27]. The Stroke in Young Adults with Sickle Cell Anemia (SPIYA) study is currently investigating HU's effectiveness in preventing stroke in Nigerian adolescents and young adults with sickle cell anemia.…”
Section: Hydroxyurea (Hu)mentioning
confidence: 99%
“…HU's effectiveness will be determined by comparing the baseline and potentially reduced TCD velocities. Preliminary study results from the SACRED study identified a higher prevalence of conditional TCD and lower abnormal TCD, which the investigators suggest could be attributed to differences in baseline status, prior treatment effects, or genetics [27]. The Stroke in Young Adults with Sickle Cell Anemia (SPIYA) study is currently investigating HU's effectiveness in preventing stroke in Nigerian adolescents and young adults with sickle cell anemia.…”
Section: Hydroxyurea (Hu)mentioning
confidence: 99%
“…The trial underscored the significance of implementing a TCD screening program in conjunction with hydroxyurea therapy to decrease the impact of SCD and strokes in resource-constrained settings [ 13 , 14 ]. The study was conducted in partnership with the Cincinnati Children's Hospital Medical Center, which also collaborated with researchers from the Dominican Republic on a similar clinical trial, Stroke Avoidance for Children in REpública Dominicana (SACRED), on the efficacy of hydroxyurea in reducing TCD velocities [ 15 ]. Hematopoietic SCT offers the potential for stopping transfusion therapy, but its benefits have not been established.…”
Section: Reviewmentioning
confidence: 99%